Evaluasi Kualitas Kompos Limbah Baglog Jamur Tiram Berbasis Standar Nasional Indonesia dan Uji Perkecambahan Benih pada Tanah Sulfat Masam - Putri, Komala Aminda; Jumar, Jumar; Saputra, Riza Adrianoor (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Oyster mushroom baglog waste that is not used properly will cause problems such as environmental pollution, and can also be a source of pollution for cultivated oyster mushrooms. Composting is an alternative to the management of oyster mushroom baglog waste. However, the compost must also be of good quality, the quality of the compost can be determined both by the physical and chemical properties of compost. Given the importance of compost quality, compost must refer to the standard criteria that have been determined. Therefore, this research aims to evaluate the physical quality (temperature, aroma, and color) and chemical (pH, organic C, total N, ratio C/N, total P, and total K) compost of oyster mushroom baglog waste based on the Indonesian National Standard (SNI) 19-7030-2004, corn seed germination, and rice root growth on acid sulfate soil applied to oyster mushroom baglog waste compost. The results showed that the compost of oyster mushroom baglog waste had complied with the SNI, where the parameters of the compost had met SNI, namely: temperature 33 oC, blackish-brown color, smell like soil, organic C 14.38%, N 0.74%, ratio C/N 19.43, P 0.50%, K 0.35%, and the percentage of germination of corn seeds of Exsotic Pertiwi Varieties was 97% of germinated seeds. The application of oyster mushroom baglog waste compost at a dose of 20 ton.ha-1 was able to increase the root length of rice in acid sulfate soils.